Advanced automated fibre placement - Krombholz, Christian; Delisle, Dominik; Perner, Marcus (Cranfield University Press, 2013)
The further increase of production rates while maintaining or improving quality and lower costs demand the development of new manufacturing solutions. For this purpose, within the project GroFi® the German Aerospace Center (DLR) develops a new plant, processes and sensor systems that enable a productive, cost-reducing manufacturing with an increase in quality of large-scale composite structures. The plant concept is a novel robot-based multi-head fibre placement facility, that coordinates its up to 8 layup units working on one or more components simultaneously. For the coordination of these layup units a closed CAD-CAM simulation was developed, that generates a time and / or cost-effective manufacturing process. To increase quality and productivity additionally, a comprehensive sensor system has been developed. This development of the DLR in the field of an advanced automated fibre placement technology serves the requirements of the current aviation industry.
Keywords: Automated Fibre Placement Technology; Sensor System; CAD-CAM Simulation